GE_GERICHTE A/1069/2022 vom 7. April 2022 - GE Cour de justice (2022)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEtr.75.al1.leth; LEtr.76.al1.letb.ch1; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4; LEI.75.al1.letb; LEI.74